Double immune checkpoint blockade in advanced NSCLC. (August 2020) - Mariniello, Annapaola; Novello, Silvia; Scagliotti, Giorgio V; Ramalingam, Suresh S
Graphical abstract: Highlights: In NSCLC, immunotherapy with checkpoint inhibitors has proven successful. To extend clinical benefit, many immunotherapy-based combinations were developed. Blockade of CTLA-4 and PD-1 targets complementary pathways in T cell activation. Checkmate 227 trial reported OS benefit with front-line nivolumab and ipilimumab. Many issues related to patient selection and sequencing remain unaddressed. Abstract: Immunotherapy-based options for patients with advanced non-small cell lung cancer (NSCLC) are increasing at an unprecedented pace, carrying the promise to prolong survival of this deadly disease. To maximize responses and extend benefit to a larger portion of patients, immunotherapy combination strategies are currently under investigation, with chemo-immunotherapy already in use. Combinations of programmed death-1/ligand-1 (PD-1/L1) and cytotoxic T lymphocytes antigen-4 (CTLA-4) were developed with the rationale of targeting complementary pathways involved in T cell activation, and already showed to be highly active in other malignancies. Recently, the phase III Checkmate 227 trial showed that combination of nivolumab and ipilimumab provided survival benefit in untreated advanced NSCLC patients. However, accurate patients' selection and appropriate sequencing of different immunotherapy-based approaches remain unsolved. In this review, we provide an overview of the currently available evidence on double immune checkpoint inhibition (ICI) for NSCLC treatment and discuss current issues and future perspectives.